Los puntos suspensivos de un jusnaturalista atípico. A propósito del último libro de Andrés Ollero, Entre el Derecho y la vida pública - García Figueroa, Alfonso J. (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This paper gives a critical account of Andrés Ollero's book, Entre el Derecho y la vida pública (Between Law and Public Life). It follows the bio-biography that the author himself shows us in his book, but pointing out possible objections to the political, institutional and theoretical positions of Andrés Ollero.
Keywords: Constitutional Court; iusnaturalism; legal positivism